LOGOTERAPI EFEKTIF UNTUK MENURUNKAN TINGKAT DEPRESI: STUDI META-ANALISIS - Rosa Bany Widiaratri; Ananta Yudiarso (JIP (Jurnal Intervensi Psikologi), 2022)
Depression is one of the problems in mental health that is currently experienced by many individuals around the world Logotherapy is a method of psychological intervention that focuses on self-empowerment through finding the meaning of one's life. This study aims to examine the level of effectiveness and impact of logotherapy in reducing the level of depression in individuals. This study used 13 studies of scientific journals that would test by meta-analysis technic. The main data used in this study were the number of participants (N), the average after the intervention (M), and the standard deviation (SD). Further testing involved the intensity of the number of intervention sessions given as a moderating variable. Based on the test results, logotherapy is effective in reducing the level of depression significantly with the effect size obtained through the random effect model g=-1.93, and the significance is <0.01. The presence of the intensity variable of the number of sessions did not have a large and significant impact on the ability of logotherapy to reduce the level of depression with a moderator effect size of g=-0.140.